Processing of unstable bacteriophage T4 gene 32 mRNAs into a stable species requires Escherichia coli ribonuclease E. - Mudd, E A (1988)
Gene 32 from bacteriophage T4 is transcribed as precursor transcripts which are processed to a stable product. This processing of the gene 32 mRNA was observed in RNase III or P-deficient strains of Escherichia coli. However, after infection of an RNase E-deficient strain, the amount of processed transcript was significantly reduced while the levels of the precursor transcripts remained high. RNase E therefore appears to have an essential role in the processing of the gene 32 mRNA. We have mapped the exact 5' end of the processed transcript by primer extension. The cleavage occurs near a stem-loop structure at a site which shows some similarity to other known RNase E cleavage sites. The effects of the processing on the differential stability of the upstream and downstream sequences, and on gene expression, are discussed.